Impact of Proactive Personality on Affective Commitment: Mediation Effect of Job Satisfaction - Tajammal Hussain Awan; Muhammad Adeel Abid; Muhammad Shahzad Aslam; Muhammad Mohsin Hafeez; Muhammad Shahzad Akram (iRASD Journal of Management)
Organizations are finding it harder and harder to improve their performance amid fierce competition. Globalization is causing markets to transition from traditional to digital, and as new things are developed, product lifecycles are getting shorter. Organizations don't always grow in the same way. The political, social, and environmental factors make doing business in developing nations very challenging. Business studies courses emphasize the role of staff in overcoming issues like this. Proactive workers look for a company that can adapt to their work and environmental situations. According to this study, individuals' proactive personalities under the effect of perceived organizational support result in affective commitment by job satisfaction. Through a Google form, 221 respondents in managerial positions were randomly selected from manufacturing and service firms. SPSS V.20 was employed for the data analysis. Using the Hayes method, mediation and moderated mediation analysis. The findings indicate a connection between proactive personality and emotional commitment through job satisfaction, and that this connection will become stronger as perceived organizational support increases. Proactive personality with affective commitment are partially mediated. Empirically, all three of the study's hypotheses were confirmed. Managers and practitioners will benefit from this study's decision-making advice.